UPAYA PERLINDUNGAN HUKUM TERHADAP STATUS TANAH YANG MENJADI JALAN TANI TANPA AKTA IKRAR WAKAF: STUDI DI DESA WATUAMPARA KABUPATEN BUTON SELATAN - Zamrud Wa Ode; Hamdu Rizal Saputra (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The resolution of disputes over waqf (endowment) without a waqf declaration deed has significant legal implications, as regulated by Law No. 41 of 2004 on Waqf. Land endowed without a waqf declaration deed lacks clear legal force, which can lead to uncertainty regarding the status of the land and potential disputes in the future. This study examines the importance of the waqf declaration deed as valid evidence of the intention to endow property, as well as a requirement to ensure the validity and protection of rights over waqf land. The case in Watuampara Village serves as a real example of how unclear land status can lead to conflicts among interested parties. Preventive measures against disputes are crucial and should be conducted through socialization and education regarding the waqf declaration deed and the registration of waqf land. Additionally, dispute resolution can be carried out through non-litigation methods, such as deliberation, or through litigation if deliberation does not yield results. This study concludes that to avoid legal risks and potential disputes, it is essential for parties wishing to endow land to promptly execute a waqf declaration deed in accordance with applicable regulations.